1989
DOI: 10.2307/3430549
|View full text |Cite
|
Sign up to set email alerts
|

Review, Discussion, and Summary: Toxicology

Abstract: The research presented in the toxicology session of the Symposium on the Health Effects of Acid Aerosols significantly advances our understanding of the health effects of acid aerosols and clearly illustrates the importance of animal inhalation toxicology to risk assessment. The description of the effects of acid on airway mucus buffering capacity and viscosity helps explain some of the mechanisms responsible for the effects of sulfuric acid on mucociliary clearance and pulmonary function observed in man and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These include changes in pulmonary function, diminished lung defense and impaired mucociliary clearance, as well as obstructive, inflammatory, and neoplas-tic disease. These topics have been the subjects of several excellent recent reviews (128)(129)(130)(131)(132). This section will focus on specific effects of air pollutants on airway mucus function, secretion, and biosynthesis, as they pertain to the development of pulmonary toxicology and disease.…”
Section: Effects Of Air Pollutants On Airway Mucusmentioning
confidence: 99%
“…These include changes in pulmonary function, diminished lung defense and impaired mucociliary clearance, as well as obstructive, inflammatory, and neoplas-tic disease. These topics have been the subjects of several excellent recent reviews (128)(129)(130)(131)(132). This section will focus on specific effects of air pollutants on airway mucus function, secretion, and biosynthesis, as they pertain to the development of pulmonary toxicology and disease.…”
Section: Effects Of Air Pollutants On Airway Mucusmentioning
confidence: 99%
“…This severe constraint raises a host of methodologic problems, but the potential value of morphometric measurements argues in favor of further exploring this promising technique. For example, morphometry has been used to study postnatal lung growth (1), an outcome relevant to ETS-NO2 exposur; and numerous morphometric studies have found pulmonary changes in animals exposed to single pollutants and pollutant mixtures (10). Limited studies of air pollution using morphometry with human autopsy specimens point to the feasibility of moving from animal to human tissues.…”
Section: Noninvasive Markersmentioning
confidence: 99%